Deficiency and dysfunctional roles of natural killer T cells in patients with ARDS - Park, Ki-Jeong; Kim, Tae-Ok; Cho, Young-Nan; Jin, Hye-Mi; Jo, Young-Goun; Shin, Hong-Joon; Kho, Bo Gun; Kee, Seung-Jung; Park, Yong-Wook (Frontiers in Immunology, 2024)
Objective: Acute respiratory distress syndrome (ARDS) presents a global health challenge, characterized by significant morbidity and mortality. However, the role of natural killer T (NKT) cells in human ARDS remains poorly understood. Therefore, this study explored the numerical and functional status of NKT cells in patients with ARDS, examining their clinical relevance and interactions with macrophages and fibroblasts during various stages of the syndrome. Methods: Peripheral blood from 40 ARDS patients and 30 healthy controls was analyzed, with paired samples of peripheral blood and bronchoalveolar lavage fluid (BALF) from seven ARDS patients. We measured levels of NKT cells, cytokines, CD69, programmed death-1 (PD-1), and annexin-V using flow cytometry, and extracellular matrix (ECM) protein expression using realtime PCR. Results: ARDS patients exhibited decreased circulating NKT cells with elevated CD69 expression and enhanced IL-17 production. The reduction in NKT cells correlated with PaO2/FiO2 ratio, albumin, and C-reactive protein levels. Proliferative responses to α-galactosylceramide (α-GalCer) were impaired, and co-culturing NKT cells with monocytes or T cells from ARDS patients resulted in a reduced α-GalCer response. Increased and activated NKT cells in BALF induced proinflammatory cytokine release by macrophages and ECM protein expression in fibroblasts. Conclusion: ARDS is associated with a numerical deficiency but functional activation of circulating NKT cells, showing impaired responses to α-GalCer and altered interactions with immune cells. The increase in NKT cells within BALF suggests their role in inducing inflammation and remodeling/fibrosis, highlighting the potential of targeting NKT cells as a therapeutic approach for ARDS.